Elements of Quantum Optics - Meystre, Pierre; Sargent, Murray; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Elements of Quantum Optics gives a self-contained and broad coverage of the basic elements necessary to understand and carry out research in laser physics and quantum optics, including a review of basic quantum mechanics and pedagogical introductions to system-reservoir interactions and to second quantization. The text reveals the close connection between many seemingly unrelated topics, such as probe absorption, four-wave mixing, optical instabilities, resonance fluorescence and squeezing. It also comprises discussions of cavity quantum electrodynamics and atom optics. The 4th edition includes a new chapter on quantum entanglement and quantum information, as well as added discussions of the quantum beam splitter, electromagnetically induced transparency, slow light, and the input-output formalism needed to understand many problems in quantum optics. It also provides an expanded treatment of the minimum-coupling Hamiltonian and a simple derivation of the Gross-Pitaevskii equation, an important gateway to research in ultracold atoms and molecules.
Classical Electromagnetic Fields -- Classical Nonlinear Optics -- Quantum Mechanical Background -- Mixtures and the Density Operator -- CW Field Interactions -- Mechanical Effects of Light -- to Laser Theory -- Optical Bistability -- Saturation Spectroscopy -- Three and Four Wave Mixing -- Time-Varying Phenomena in Cavities -- Coherent Transients -- Field Quantization -- Interaction Between Atoms and Quantized Fields -- System-Reservoir Interactions -- Resonance Fluorescence -- Squeezed States of Light -- Cavity Quantum Electrodynamics -- Quantum Theory of a Laser -- Entanglement, Bell Inequalities and Quantum Information.
Keywords: Physics; Elementary particles (Physics).; Quantum field theory; Quantum optics; Lasers; Photonics; Physics; Elementary Particles, Quantum Field Theory; Laser Technology, Photonics; Quantum Optics; Electronic books